首页
注册 | 登录

(x+1-1/1-x)÷(x-x #178;/x-1)(x-4/x-x-6+x+2/x-3)÷x+1/x-3

(x+1-1/1-x)÷(x-x²/x-1) (x-4/x-x-6+ x+2/x-3)÷x+1/x-3
分类:数学 2017-11-13 共 2 个回复
最佳回复
(x+1-1/1-x)÷(x-x²/x-1)
=[(x+1)+1/(x-1)]×[-(x-1)/x(x-1)]
=(x²-1+1)/(x-1)×(-1/x)
=-x/(x-1)

(x-4/x²-x-6+ x+2/x-3)÷x+1/x-3
=[(x-4)+(x+2)²]/(x+2)(x-3)×(x-3)/(x+1)
=(x²+5x)/(x+2)(x+1)
其它回复
①(x+1-1/1-x)÷(x-x²/x-1)
=[(1-x²-1)/1-x]÷[(x²-x-x²)/x-1]
=(-x²/1-x)÷(-x/x-1)
=x
②(x-4/x-x-6+ x+2/x-3)÷x+1/x-3
能把式子列得清楚一点吗??


2020 及时作业本 webmaster#jeepfushi.net
10 q. 0.008 s.
湘ICP备19005923号